Genomic characterization of an Omono River virus isolated from Culex tritaeniorhynchus in eastern China - Xiaojuan Lin; Bo Sun; Guifang Liu; Yunjiao Wu; Yao Liu; Feng Ji; Zexin Tao; Aiqiang Xu (Virology Journal, 2023)
Abstract Omono River virus (OMRV) is a newly reported, unclassified RNA virus in the family Totiviridae, which infects mosquitoes and bats. In this study, we report the isolation of an OMRV strain SD76 from Culex tritaeniorhynchus captured in Jinan city, China. The cytopathic effect was characterized by cell fusion on C6/36 cell line. Its complete genome was 7611 nucleotides in length, with 71.4–90.4% similarities with other OMRV strains. Phylogenetic analysis based on complete genomes showed all OMRV-like strains can be divided into 3 groups with between-group distances ranging from 0.254 to 0.293. These results revealed that the OMRV isolate had high genetic diversity with those identified previously, and enriched the genetic information of family Totiviridae.